On the razor’s edge: the (virtual) image between illusion and deception (AN-ICON. Studies in Environmental Images [ISSN 2785-7433], 2022)
Most often, the concept of illusion has been interpreted in a negative way as a synonym for deception. However, a second, positive meaning has gained sometimes prominence according to which illusion does not necessarily imply any cognitive failure or distortion. As such, it can even play an important role in eliciting genuine aesthetic enjoyment. This introduction focuses on crucial aspects in the history and theory of aesthetic illusion, a notion that has resurfaced recently as a key aspect of the phenomenon of immersion, being regarded as a goal to be pursued by both the creators and the experiencers of virtual environments.
Keywords: Immersion; Presence; Virtual reality; Representation; Hallucination